2014
DOI: 10.1155/2014/850802
|View full text |Cite
|
Sign up to set email alerts
|

ECR-MAPK Regulation in Liver Early Development

Abstract: Early growth is connected to a key link between embryonic development and aging. In this paper, liver gene expression profiles were assayed at postnatal day 22 and week 16 of age. Meanwhile another independent animal experiment and cell culture were carried out for validation. Significance analysis of microarrays, qPCR verification, drug induction/inhibition assays, and metabonomics indicated that alpha-2u globulin (extracellular region)-socs2 (-SH2-containing signals/receptor tyrosine kinases)-ppp2r2a/pik3c3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…This may be the reason for the increased expression of the gene in the late phase of liver regeneration. A study conducted by Zhao et al [29] showed that tumor-like growth in the early phase of liver development is positively and negatively coordinated by α-2u globulin (extracellular domain)/ppp2r2a-pik3c3 (MAPK signaling pathway)/Hsd3b5 (metabolic pathway), evidently showing that Hsd3b5 gene plays an important role in the biosynthesis of all steroid hormones. In addition, another article by Xiu et al [30] also showed a significant expression decrease in Hsd3b5 after lowering serum testosterone and estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…This may be the reason for the increased expression of the gene in the late phase of liver regeneration. A study conducted by Zhao et al [29] showed that tumor-like growth in the early phase of liver development is positively and negatively coordinated by α-2u globulin (extracellular domain)/ppp2r2a-pik3c3 (MAPK signaling pathway)/Hsd3b5 (metabolic pathway), evidently showing that Hsd3b5 gene plays an important role in the biosynthesis of all steroid hormones. In addition, another article by Xiu et al [30] also showed a significant expression decrease in Hsd3b5 after lowering serum testosterone and estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the relationship between PSO dietary intervention and the occurrence and development of MD is still in the preliminary stage of observing phenomena, so the mechanism of action whereby PSO intervention alleviates MD is largely unclear. The aim of this study was to establish the MD metabolic profile and elucidate the variation law of the migration process of PSO intervention in alleviating MD, using nuclear magnetic resonance (NMR)‐based metabonomics combined with quantitative real‐time polymerase chain reaction (qPCR) to analyze lipid uptake and transport and the gene expression and protein levels of ERS, TLR (toll‐like receptor), UPR and inflammation pathways. Based on the high homology between humans and rats, the results of this study will provide basic information and reference data on MD prevention through PSO dietary intervention in the human population.…”
Section: Introductionmentioning
confidence: 99%